Growing vegetables in a warming world - a review of crop response to drought stress, and strategies to mitigate adverse effects in vegetable production - Park, Jongwon; Lee, Se-Hyoung; Lee, Joowon; Wi, Seung Hwan; Seo, Tae Cheol; Moon, Ji Hye; Jang, Seonghoe (Frontiers in Plant Science, 2025)
Drought stress caused by climate change is increasingly affecting the productivity and quality of vegetable crops worldwide. This review comprehensively analyzes the physiological, biochemical, and molecular mechanisms that vegetable crops employ to cope with drought stress. In particular, it highlights the significance of key hormonal regulation pathways, such as abscisic acid (ABA), jasmonic acid (JA), and ethylene (ET), which play crucial roles in mediating stress responses. Additionally, the role of antioxidant defense systems in mitigating oxidative damage caused by reactive oxygen species (ROS) is discussed. Advances in agricultural technologies, such as the use of smart irrigation systems and biostimulants, have shown promising results in enhancing drought resistance and optimizing crop yields. Integrating these strategies with the development of drought resistant varieties through gene editing and traditional breeding techniques will ensure sustainable agricultural production in drought stressed environments. This review aims to support future research into sustainable agricultural development to enhance drought tolerance in vegetable production and secure global food supply.